The Impact of COVID-19 on Oral Cancer Diagnosis: A Systematic Review - Riccardo Pulcini; Silvia D'Agostino; Marco Dolci; Alessandra Bissioli; Lucia Caporaso; Francesca Iarussi (Pandawa Institute, 2022)
The Coronavirus-19 pandemic has led to severe collapses in international health systems that have repercussions at all levels of disease prevention. Oral squamous cell carcinoma (OSCC) is the most common head / neck malignancy, and it is usually diagnosed late due to patients neglecting symptoms. The purpose of this systematic review is to verify the impact of Sars-Cov-2 pandemic on OSCC diagnosis. The search methodology follows the PRISMA statement performing a PubMed investigation from 2019 to 2021 using MeSH such as “Covid-19; oral cancer”. A multidisciplinary approach would be effective, with a broadening of the knowledge of health professionals to identify cancerous lesions. A timely diagnosis of OSCC is crucial and its management is fundamental also for dental specialists. With the aim to anticipate the diagnosis, it will be desirable to set prevention campaigns also by the assistance in telemedicine.